La Lesión del Principio de Integridad a través del Plan Esencial de Aseguramiento en Salud - Linares Flores, Karen Breysi (2019)
The purpose of this work is to determine if the principle of social security integrality is injured through the Essential Health Insurance Plan, that is, if there is a violation of the principle of social security integrality when a limited list of conditions is established insurable in the Essential Health Insurance Plan. The procedure used was to analyze case law of the Constitutional Court on the right to the protection of health, life, dignity and equality in relation to the principle of integrality of social security. The burden of illness that is presented in Peru and that must be covered by the Essential Health Insurance Plan was also identified. Likewise, the types of plans offered by the institutions that manage health insurance funds were compared, in order to know which insurance offers greater coverage of insurable conditions. As compared law was also analyzed to publicize the efficiency of various health systems in the world; and health professionals were interviewed to know and collect information regarding the subject under investigation, and to form a position regarding the injury of the principle of integrality through the PEAS.